Using Goal Achievement Training in juvenile justice settings to improve substance use services for youth on community supervision - Jacqueline Horan Fisher; Jennifer E. Becan; Philip W. Harris; Alexis Nager; Connie Baird-Thomas; Aaron Hogue; John P. Bartkowski; Tisha Wiley; The JJ-TRIALS Cooperative (BMC, 2018)
Abstract Background The link between substance use and involvement in the juvenile justice system has been well established. Justice-involved youth tend to have higher rates of drug use than their non-offending peers. At the same time, continued use can contribute to an elevated risk of recidivism, which leads to further, and oftentimes more serious, involvement with the juvenile justice system. Because of these high rates of use, the juvenile justice system is well positioned to help identify youth with substance use problems and connect them to treatment. However, research has found that only about 60% of juvenile probation agencies screen all youth for substance involvement, and even fewer provide comprehensive assessment or help youth enroll in substance use treatment. Method This paper describes an integrated training curriculum that was developed to help juvenile justice agencies improve their continuum of care for youth probationers with substance use problems. Goal Achievement Training (GAT) provides a platform for continuous quality improvement via two sessions delivered onsite to small groups of staff from juvenile justice and behavioral health agencies. In the first session, participants are taught to identify goals and goal steps for addressing identified areas of unmet need (i.e., screening, assessment, and linkage to treatment services). In the second session, participants learn principles and strategies of data-driven decision-making for achieving these goals. This paper highlights GAT as a model for the effective implementation of cost-efficient training strategies designed to increase self-directed quality improvement activities that can be applied to any performance domain within juvenile justice settings. Efforts to monitor implementation fidelity of GAT within the specific context of the juvenile justice settings are highlighted. Discussion Challenges to setting the stage for process improvement generally, as well as specific hurdles within juvenile justice settings are discussed, as are next steps in disseminating findings regarding the fidelity to and effectiveness of GAT in this unique context. Trial registration Clinical Trials Registration number - NCT02672150.